Ionic Liquid–Polymer Composites: A New Platform for Multifunctional Applications. (6th April 2020) - Correia, Daniela Maria; Fernandes, Liliana Correia; Martins, Pedro Manuel; García‐Astrain, Clara; Costa, Carlos Miguel; Reguera, Javier; Lanceros‐Méndez, Senentxu
Abstract: Ionic liquids (ILs) have emerged as a novel class of chemical compounds for the development of advanced (multi)functional materials with outstanding potential in applications of several areas due to their unique properties and functionalities. The combination of ILs with polymers, in a composite, allows for developing smart materials, which synergistically combine the features of specific polymers and ILs. Moreover, ILs can be extensively modified by the incorporation of functional groups with specific properties into the cation, anion, or both. Thus, it is possible to tune the IL, the polymer, or both to obtain a broad spectrum of multifunctional composites and address the specific requirements of many applications. This work focusses on advanced materials and strategies concerning ILs and polymers for the development of smart IL/polymer‐based materials for applications including responsive and sensitive sensors, actuators, environment, batteries, fuel cells, and biomedical applications. Abstract : Based on their interesting properties, ionic liquids (ILs) are used for the development of polymer‐based multifunctional materials. The suitable combination of both IL and polymer properties allows for developing advanced materials with tailored functional responses and applicability in areas including sensors and actuators, environment (air and water remediation), energy generation and storage, and biomedicine.